Drug cartels respond to the pandemic - Luane Santana Ribeiro; Daniel de Medeiros Gonzaga; Matthijs Pieter van den Burg; Juan Gérvas (Sociedade Brasileira de Medicina de Família e Comunidade, 2021)
More than 13.6 million Brazilians live in large poor communities known as favelas. Historically, these territories suffer due to social rights insufficiency and violent conflicts orchestrated by the police and the drug cartels. In this context, the dismantling of the public health care system and denialism of the pandemic by the federal government increases the vulnerability within the favelas during the COVID-19 crisis. Although the federal government failed to take up measures to control the transmission of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), a criminal organization that dominates the trafficking of drugs in several Brazilian favelas, known as Comando Vermelho, instead dictated those protective actions. This study aimed to discuss the ethical aspects of the relationship between primary health care professionals and the drug cartels in order to promote health care in the favelas.